New developments in Hong Kong's anti-money laundering laws. Issue 3 (4th July 2016) - Kwok, David
Abstract : Purpose: The purpose of this paper is to discuss briefly new developments in Hong Kong's anti-money laundering laws, both in terms of case law and legislation. Design/methodology/approach: In terms of case law, I discuss two decisions given by HK's Court of Final Appeal relating to the dealing of proceeds of crime offence. Also, a guideline case on sentencing is also examined. In terms of legislation, I briefly outline the main provisions of the newly enacted Anti-Money Laundering and Counter-Terrorist Financing (Financial Institutions) Ordinance. Findings: As suggested by the FATF, new measures need to be put in place. The AML laws as they presently stand need further improvement. Originality/value: A good AML regime is necessary as Hong Kong continues to thrive as a major financial/banking centre in Asia. This paper seeks to encourage more discussion on the topic.